Differences in Facial Skin Acidity Levels of Nurses in Sebelas Maret University Hospital, Before and After Surgical Mask Use During the COVID-19 Pandemic - Alamanda Murasmita; Meirina Mulia W; Maria Galuh K; Dita Eka N; Ervina Rosmarwati (HM Publisher, 2023)
Background: Indonesia has reported more than 4 million confirmed COVID-19 cases as of November 2021. This has led to an increase in the use of personal protective equipment (PPE), for example, surgical masks in hospitals, especially referral hospitals for COVID-19 patients. The Potential Hydrogen (pH) or level of acidity plays an important role in the body's physiological functions and regulates the formation of an epidermal barrier (stratum corneum). Thus, the use of surgical masks is able to influence the pH of human skin. This study aimed to determine the difference in facial skin acidity (pH) levels of nurses at Sebelas Maret University Hospital before and after surgical mask use. Methods: The study utilized a cross-sectional observational method and was conducted at the Sebelas Maret University Hospital, Surakarta. A total of 55 subjects were involved in this study, and each subject’s facial skin Potential Hydrogen (pH) was measured before and after surgical mask use. Subsequently, all data were analyzed with a T-test using SPSS 21.00, and a p-value <0.05 indicated statistical significance. Results: The results showed facial skin pH increased after surgical mask use for nurses at the Sebelas Maret University Hospital (p = 0.000). Conclusion: An increase in the physiological value of skin pH was observed in the nurses of Sebelas Maret University Hospital after surgical mask use.